Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If cot A+ tan A = m sec A – cos A = n , prove that: (m 2 n) 2/3 -(mn 2 ) 2/3 = 1.


If cot A+ tan A = m sec A – cos A = n , prove that:
(m2n)2/3-(mn2)2/3 = 1.

Grade:10

1 Answers

Arun
25763 Points
2 years ago
Given cot theta +tan theta = m
1/tan theta+ tan theta = m.........(1)
sec theta - cos theta = n
sec theta - 1/ sec theta = n ........(2)

Using equation (1) and (2)
(m^2n)^(2/3)-(mn^2)^(2/3)
((1/tan theta+ tan theta)^2(sec theta - 1/ sec theta))^(2/3)-((1/tan theta+ tan theta)(sec theta - 1/ sec theta)^2)^(2/3)

(1/cos^6 theta)^(1/3)-(sin^6 theta/cos^6 theta)^(1/3)

sec^2 theta-tan^2 theta
=1

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free